Fundamentals of conservation biology - Hunter, Malcolm L.; Gibbs, James P.; Popescu, Viorel D. (Hoboken : Wiley, Blackwell, 2021)
'December 31, 2019: New Year's Eve and a steady snow is luring me outdoors to celebrate a 30th wedding anniversary, but first I need to draft the last few new words for our Fourth Edition. The most conspicuous new feature is the addition of Viorel Popescu as an author, continuing a tradition of extending academic lineages, given that Viorel earned graduate degrees with both James and me. Undertaking a collaboration like this requires considerable trust and James and I knew that Viorel had the talent and commitment to make a huge contribution to the book, leading the revision of four key chapters and carefully reviewing all of the chapters. Furthermore, he brought to the table many new perspectives as a native of another part of the world - Romania - where he remains active in conservation at many levels'--
Keywords: Conservation biology; Natural resources -- Management; Biodiversity conservation